Altered sphingolipid pathway in SARS-CoV-2 infected human lung tissue - Khan, Rabisa J.; Single, Sierra L.; Simmons, Christopher S.; Athar, Mohammad; Liu, Yuelong; Bodduluri, Sandeep; Benson, Paul V.; Goliwas, Kayla F.; Deshane, Jessy S. (Frontiers in Immunology, 2023)
The SARS-CoV-2 mediated COVID-19 pandemic has impacted millions worldwide. Hyperinflammatory processes, including cytokine storm, contribute to long-standing tissue injury and damage in COVID-19. The metabolism of sphingolipids as regulators of cell survival, differentiation, and proliferation has been implicated in inflammatory signaling and cytokine responses. Sphingosine-kinase-1 (SK1) and ceramide-synthase-2 (CERS2) generate metabolites that regulate the anti-and pro-apoptotic processes, respectively. Alterations in SK1 and CERS2 expression may contribute to the inflammation and tissue damage during COVID-19.The central objective of this study is to evaluate structural changes in the lung post-SARS-CoV-2 infection and to investigate whether the sphingolipid rheostat is altered in response to SARS-CoV-2 infection. Here, we report significant reduction in air space and increase in collagen deposition in lung autopsy tissues from patients who died from COVID-19 (COVID-19 + ) and COVID-19 convalescent individuals. Central and peripheral lung tissues from COVID-19 + or control autopsies and resected lung tissue from COVID-19 convalescents were subjected to immunohistochemical evaluation of SK1 and CERS2. SK1 expression increased in the lungs of COVID-19 + autopsies and COVID-19 convalescent lung tissue compared to controls and was mostly associated with Type II pneumocytes and alveolar macrophages. No significant difference in CERS2 expression was noted. SARS-CoV-2 infection upregulates SK1 and increases the ratio of SK1 to CERS2 expression in lung tissues of COVID-19 autopsies and COVID-19 convalescents. These data suggest an alteration in the sphingolipid rheostat in lung tissue during COVID-19, suggesting a potential contribution to the inflammation and tissue damage associated with viral infection.